Seinfeld. Season 6 [videorecording (DVD)] - Seinfeld, Jerry; Louis-Dreyfus, Julia; Richards, Michael, 1949-; Alexander, Jason, 1959- (Sony Pictures Home Entertainment, 2005)
Jerry and his friends are still dealing with everyday life and discussing various quirky situations that we can all relate to (especially if living in New York City). The eccentric personalities of the offbeat characters who make up Jerry's social circle contribute to the fun.